Neurocognitive dysfunction in children with β thalassemia major: psychometric, neurophysiologic and radiologic evaluation. Issue 10 (26th November 2017) - Elalfy, M. S.; Aly, R. H.; Azzam, H.; Aboelftouh, K.; Shatla, R. H.; Tarif, M.; Abdatty, M.; Elsayed, R. M.
ABSTRACT: Objective: To evaluate the impact of iron chelating drugs and serum ferritin on the neurocognitive functions of patients with β thalassemia major (β-TM), using psychometric, neurophysiologic and radiologic tests. Methods: Eighty children with β-TM were enrolled into the study and were compared to 40 healthy controls. All participants were evaluated by measuring serum ferritin, neurocognitive assessment by Benton Visual Retention Test, Wechsler Intelligence Scale for Children, Wisconsin Card Sort Test, P300 and magnetic resonance spectroscopy (MRS). Results: WISC in our study showed that 40% of cases were borderline mental function as regards total IQ. Neurophysiologic tests were significantly impaired in patients compared to control group, with significant impairment in those receiving desferrioxamine (DFO). P300 amplitude was significantly lower in cases compared to controls (2.24 and 4.66 uv, respectively), recording the shortest amplitude in patients receiving DFO. Altered metabolic markers in the brain were detected by MRS in the form of reduced N -acetylaspartate to creatine ratio in 78.3% of our cases. There were significant correlations between psychometric tests and both neurophysiologic (P300) and radiologic (MRS) tests. Conclusion: β-TM is associated with neurocognitive impairment that can be assessed by psychometric, neurophysiologic and radiologic tests. The role of hemosiderosis and iron chelation therapy on cognitive functioning still need more research. Abbreviations: β-TM: beta thalassemia major; DFO: Dysferal; DFP: Deferiprone; DFX: Deferasirox; WISC: Wechsler Intelligence Scale for Children; VIQ: verbal IQ; PIQ: performance IQ; TIQ: total IQ; BVRT: Benton Visual Retention Test; WCST: Wisconsin Card Sort Test; MRS: Magnetic resonant spectroscopy; NAA/Cr ratio: N-acetylaspartate to creatine ratio